A relação entre o posicionamento estratégico e as dimensões de sucesso em projetos: estudo de caso de uma subsidiária brasileira de empresa multinacional do ramo de autopeças - Banzato, Carlos Roberto (2014)
Among several strategy concepts, one of the most common is that define strategy as a top management plan to achieve results linked with company mission and the general targets of the organization. A robust business strategy must answer questions like where we compete, how gain and maintain competitive advantage, what organizational capabilities are needed, what is the organization status and what is needed to change it. Program management assume important role in the transformation process that organizations need to face. The only way that organizations have to implement a robust strategy and gain competitive advantage is through projects. Projects are not activities that must be finished on time but are processes related to business environment that must accomplish organization goals. Project success must be understood as a multidimentional and strategic concept. Each project must has more than one dimension to evaluate the success and such dimentions change according the importance. A wide project evaluation regarding success that cover short term and long term aspects can be defined by five dimentions: project eficciency, customer/user impact, project team impact, commercial/organizational success and preparation to the future. The methodology used in this dissertation was case study and treat about the relationship between strategic positioning and the project succes dimensions related to the business unit located in Brazil that belongs to an autopart multinational company. The findings showed a relationship between the strategic positioning and the five dimensions of success and gaps between strategy definition and strategy execution. Study findings were presented in the organization that was focus of the study in order to improve the strategic planning process.